Safety Helmet Implementation with Centralized Information System on Remote Monitoring Applications - Illahi, Alvinas Deva Sih; Bella, Anatasya; Hadiyoso, Sugondo; Aulia, Suci (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 1 April 2018DO - 10.24843/LKJITI.2018.v09.i01.p01, 2018)
Personal Protective Equipment (PPE) is standard equipment that required to ensure safety of workers. PPE equipment that used during work such as: Safety helmet, safety glass, and ear plug. PPE that being used by workers doesn’t informative yet, only serve as personal protective so evacuation prevention still looks difficult to do prior accident happened. In this research, Safety Helmet Project has been implemented with pulse sensor, temperature sensor, carbon monoxide gas sensor, and transmission media which able transmitting data to control and monitoring center. The system also supports multiuser monitoring applications that can be accessed simultaneously through the internet network. Based on test results, the comparison of measurement gap with standard tool has been obtained as temperature sensor is 0,07%, heart sensor is ± 4%. Accuracy level for temperature sensor and heart rate are 99,67% and 95,45% by various condition of test. Another test is delay of the transmitting sensor data to the website around ± 10 seconds and controlling around ± 5 seconds.